From the patient to the population: Use of genomics for population screening - Mighton, Chloe; Shickh, Salma; Aguda, Vernie; Krishnapillai, Suvetha; Adi-Wauran, Ella; Bombard, Yvonne (Frontiers in Genetics, 2022)
Genomic medicine is expanding from a focus on diagnosis at the patient level to prevention at the population level given the ongoing under ascertainment of high-risk and actionable genetic conditions using current strategies, particularly hereditary breast and ovarian cancer (HBOC), Lynch Syndrome (LS) and familial hypercholesterolemia (FH). The availability of large-scale next-generation sequencing strategies and preventive options for these conditions makes it more feasible to screen pre-symptomatic individuals through public health-based approaches, rather than restricting testing to high-risk groups. This raises anew, and with urgency, questions about the limits of screening as well as the moral authority and capacity to screen for genetic conditions at a population level. We aimed to answer some of these critical questions by using the WHO Wilson and Jungner criteria to guide a synthesis of current evidence on genomic population screening for HBOC, LS and FH.